Ochratoxin A in foods of animal origin - GOVARIS (Α. ΓΚΟΒΑΡΗΣ), A.; SOLOMAKOS (Ν. ΣΟΛΩΜΑΚΟΣ), N.; PAXARA (Α. ΠΕΞΑΡΑ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Ochratoxin A (OTA) is a mycotoxin produced by the fungi Aspergillus ochraceus καιPénicillium verrucosum. OTA shows a nephrotoxic, teratogenic, immunotoxic and carcinogenic action against animals and humans. In humans, OTA is implicated in the aetiology of Balkan endemic nephropathy. OTA can be mainly found in foods of animal origin as a result of indirect transmission from animals exposed to naturally contaminated feed. Results from research works in various countries showed that the pork meat was the most important source of human contamination with OTA, as compared to other products of animal origin. Sausages containing blood or pork kidney presented the highest amounts of OTA among other food products of animal origin. The presence of OTA in cow's milk was rather low, since the bacteria in the rumen of ruminants are capable of splitting OTA to ochratoxin a, which is generally accepted as no toxic metabolite. The European Union has not yet set limits of ochratoxin in foods of animal origin, in contrast to these of limits in foods of plant origin.